Convenient links for the estimation of hedonic price indexes: the case of unique, infrequently traded assets - Ramalho, E.A.; Ramalho, J. J. S. (Statistica Neerlandica, 2014)
Hedonic methods are a prominent approach in the construction of quality-adjusted price indexes. This paper shows that the process of computing such indexes is substantially simplified if arithmetic (geometric) price indexes are computed based on exponential (log-linear) hedonic functions estimated by the Poisson pseudo-maximum likelihood (ordinary least squares) method. A Monte Carlo simulation study based on housing data illustrates the convenience of the links identified and the very attractive properties of the Poisson estimator in the hedonic framework.